Commercialization or Engagement: Which Is of More Significance to the U.S. Economy ? - Martin Kenney (The Research Institute of the Finnish Economy (ETLA), 2013)
Beginning with the commercialization of genetic engineering (biotechnology) research beginning in the late 1970s and the passage of the Bayh-Dole Act, U.S. university administrators quickly built technology licensing (transfer) offices meant to commercialize inventions made by their researchers. By studying technology transfer in electrical engineering and computer science, statistics and mathematics, scientific instruments, and agriculture, this article demonstrates that biotechnology model does not accurately portray the ways in which most university technology is transferred to society. The application of the biotechnology/technology licensing office model to other university disciplines may stifle the diffusion of technology to society due to undue restrictions in the flow of technology; both from the university to society and, as important, the flow of ideas and resources from society to the university. Finally, it cautions against making wholesale changes in current institutional arrangements on the basis of the current U.S.-centric model based on biotechnology. For European policy-makers, the temptation to follow the U.S biotechnology-derived model may disrupt long-standing and quite successful channels of information transfer, while not bringing the supposed benefits of the U.S. model. This is particularly true because research on European university technology transfer is still at a very early stage
Keywords: 330